PROBLEMS ENCOUNTERED IN THE TRANSLATION OF NOTARIAL DOCUMENTS FROM UZBEK TO GERMAN AND THEIR SOLUTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the main problems encountered in the translation of notarial documents from Uzbek into German and their solutions. It highlights how terminological differences, cultural and legal differences and structural changes affect the quality of translation. Strategies such as functional equivalence, explanatory translation and cultural adaptation are proposed to solve the problems. The article highlights the legal literacy and cultural sensitivity of the translator as an important factor. The study serves to strengthen the scientific foundations of legal translation in translation theory and practice.